Study of relationship between dose, LET and the risk of brain necrosis after proton therapy for skull base tumors. (October 2021) - Garbacz, Magdalena; Cordoni, Francesco Giuseppe; Durante, Marco; Gajewski, Jan; Kisielewicz, Kamil; Krah, Nils; Kopeć, Renata; Olko, Paweł; Patera, Vincenzo; Rinaldi, Ilaria; Rydygier, Marzena; Schiavi, Angelo; et al.
Highlights: We studied the relationship between variable RBE, LETd and brain radiographic changes. The extended PTV + 5 mm covers on average larger volume of necrosis than primary PTV. vRBE-weighted doses exceeded dosimetric limits in temporal lobes for >50% patients. Voxel-based analysis did not reveal association between LET and radiographic changes. Our study does not confirm the influence of the high DRBE /LETd on necrosis occurrence. Abstract: Purpose: We investigated the relationship between RBE-weighted dose (DRBE) calculated with constant (cRBE) and variable RBE (vRBE), dose-averaged linear energy transfer (LETd) and the risk of radiographic changes in skull base patients treated with protons. Methods: Clinical treatment plans of 45 patients were recalculated with Monte Carlo tool FRED. Radiographic changes (i.e. edema and/or necrosis) were identified by MRI. Dosimetric parameters for cRBE and vRBE were computed. Biological margin extension and voxel-based analysis were employed looking for association of DRBE(vRBE) and LETd with brain edema and/or necrosis. Results: When using vRBE, Dmax in the brain was above the highest dose limits for 38% of patients, while such limit was never exceeded assuming cRBE. Similar values of Dmax were observed in necrotic regions, brain and temporal lobes. Most of the brain necrosis was in proximity to the PTV. The voxel-based analysis did not show evidence of an association with high LETd values. Conclusions: When looking at standard dosimetric parameters, the higher dose associated with vRBE seems to be responsible for an enhanced risk of radiographic changes. However, as revealed by a voxel-based analysis, the large inter-patient variability hinders the identification of a clear effect for high LETd.